(untitled) (Stockholm, 2003)
This volume of Scandinavian Studies in Law is devoted to legal problems relating to taxation. The book comprises twenty-four articles covering many different areas of national and international taxation. The contributions are all written by scholars in the Scandinavian countries Denmark, Finland, Norway & Sweden. The Scandinavian countries all have comprehensive social welfare systems and huge public sectors - this has resulted in high standards for social security, but also in some of the world's highest taxes. As a consequence, Scandinavian tax laws are frequently debated in the political arena
Keywords: Taxation (Scandinavian law),Taxation,Luật thuế (Luật pháp Bắc Âu); Law and legislation